Role of Red Cell Distribution Width and Platelet Count Ratio to Predict the Severity and Outcome in Acute Pancreatitis (Bangladesh Medical Journal, 2023)
Clinical course of acute pancreatitis (AP) varies widely, its clinical features exhibit very low sensitivity for the prediction of severity of disease which is associated with high morbidity and mortality. Several single or multi parameter scoring systems have been described to evaluate the severity of AP. But sometimes, it is not clinically practicable to use these scoring systems for evaluation. This study aimed to find out the Role of Red Cell Distribution Width and Platelet Count Ratio (RPR) to predict the Severity and Outcome in AP. This prospective longitudinal study was carried out from July 2019 to July 2020, at the in-patient department of Gastrointestinal, Hepatobiliary and Pancreatic Disorders, BIRDEM General Hospital, Dhaka. Total 100 patients with AP were included for this study according to selection criteria. An informed written consent was taken from all the participants. Detail history was taken and thorough physical examination was done along with relevant laboratory investigations. Ranson's score, Modified Glasgow score, Bedside index of severity in acute pancreatitis (BISAP), red cell distribution width and platelet count ratio (RPR) were calculated. All data were recorded and analyzed by Statistical package for social sciences (SPSS) 23. In this study 44% patients were more than 60 years with a mean age of 51.34 (±15.45) year. More than two thirds patients were (67%) male. In mild acute pancreatitis  mean value of Ranson's score, BISAP score and modified Glasgow score was 0.79 (±0.14), 0.90 (±0.1) and 0.80 (±0.14) and 3.29 (±1.16), 1.77 (±0.46) ,2.74 (±0.69) in moderate to severe pancreatitis respectively with statistically difference were found in both severities (p